The Use of Kahoot to Improve Students' Narrative Text Reading Comprehension - Ayu Aprilia; Sulistyaningsih Sulistyaningsih; Lailatul Musyarofah (International Journal of English and Applied Linguistics (IJEAL), 2023)
This research discusses the usage of a game-based learning media to solve the problem of reading comprehension score poorly, namely Kahoot!. The objective of this research was to improve the students’ narrative text reading comprehension by using Kahoot as a media in the teaching and learning process. This research was classroom action research. The research was conducted to 25 students of eighth graders of Nusantara Krian junior high school. The research showed that by using Kahoot as media in the classroom learning could improve the students' narrative text reading comprehension. The students’ mean score on the pre-test was 64 and only 9 (36%) students were able to pass the minimum completeness criteria (KKM). The result score was under the KKM set by the school 75. The learners' mean score improved after the first cycle, rising to 71.2 and 13 (52%) students passed KKM. However, it showed still under minimum completeness criteria. It was therefore necessary for the second cycle, during which the score rose to 79,6 and 20 (80%) students passed the KKM. It was concluded that using Kahoot can improve the student’s narrative text reading comprehension. The students’ positive response to the usage of Kahoot in teaching and learning reinforced the improvement in the students' achievement.